PENGARUH KUALITAS KEHIDUPAN KERJA (QUALITY OF WORK LIFE), MOTIVASI KERJA, DISIPLIN KERJA TERHADAP KINERJA KARYAWAN ( Studi Kasus pada CV Dharma Utama- Duta Catering, Batu ) - Lina Apriana; Hadi Sunaryo; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACT            This stud aims to examine and analyze the effect of quality of work life, work motivation, work discipline on employee performance CV Dharma Utama- Duta Catering Batu either partial or together. The population and sample is all employees of CV Dharma Utama- Duta Catering which amounts to 82 person. The data colection through questionnaries. In this study data analysis using SPSS 14.0 version. The technique sampling using a questionnaries with a rating scale rikert and mechanical testing data used in this study include validity test, normality test, classic assumption test, multiple linier regression analysis, F test, t test.                                                                                                                         The results of the analysis show that the quality of work life significantly influence the employee performance, while motivation and work discipline does not significant effect on employee performance. It show that the quality of work life, motivation, work discipline significantly influence the performance of employees.Keyword: Quality  of  Work  Life,  Motivation,  Work  Discipline,  Performance.